Widening the spectral range of ultrahigh field enhancement by efficient coupling of localized to extended plasmons and cavity resonances in grating geometry - Mohammad Abutoama (2020)
Excitation of localized via extended plasmons was shown recently to reveal ultrahigh electromagnetic field (EM) enhancement when optimum coupling is obtained in the prism configuration. Using grating coupling, one expects several advantages over the prism scheme such as being planar, more compact, and most important the possibility of tuning the spectral range over which the enhancement occurs. In this work we show that via gratings coupling the EM field enhancement can be up to 3 orders of magnitude higher than that obtained using free space excitation of localized surface plasmons (LSPs). Furthermore, the spectral range over which the ultrahigh enhancement achieved becomes wider by tuning the grating parameters. The cavity resonances generated by thick enough gratings couple to the LSPs producing ultrahigh local enhancement and play an important role in widening the spectral range to cover the range 400–2000 nm. This is important for solar energy harvesting and improving the efficiency of infrared optoelectronic devices. Having the periodic NPs arrangement on top of the grating was found to be very significant not only under transverse magnetic (TM) polarization but also under transverse electric (TE) polarization, thus reducing the dependence on the polarization.